Nielegalna imigracja z perspektywy występku umożliwienia lub ułatwienia pobytu na terytorium Rzeczypospolitej Polskiej - Filipowska-Tuthill, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This article is devoted to the important and very current problem of immigration, from the perspective of European Union and Polish regulations. This paper analyzes the crime of enabling and facilitating the illegal stay on the Polish territory, where the perpetrator acts for personal or financial gain. The subject here is the protection of public safety and order against unauthorized aliens. Illegally staying in the Republic of Poland, foreigners create a broad spectrum of threats to the state and its citizens from administrative to illegal employment in organized crime and international terrorism.
Keywords: imigracja; nielegalni cudzoziemcy; prawo karne